A triple-targeting delivery system carrying two anticancer agents. Issue 37 (8th July 2021) - Li, Hui; Lee, Chang-Hee; Shin, Injae
Abstract : To improve tumor selectivity, we prepared a new triple-targeting delivery system bearing two anticancer agents. Both anticancer agents in this system are released in the presence of both H2 O2  and cathepsin B which are highly produced in cancer cells. Abstract : To improve tumor selectivity, a triple-targeting delivery system (Oct-FK(PBA-Az)-Dox) carrying two anticancer agents (apoptozole (Az) and doxorubicin (Dox)) was designed and synthesized. The results showed that both anticancer agents in Oct-FK(PBA-Az)-Dox are liberated in the presence of both H2 O2 and cathepsin B, which are normally present at high levels in tumors.